2020
DOI: 10.1007/s10649-020-10007-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning actions indicating algebraic thinking in multilingual classrooms

Abstract: This article discusses algebraic thinking regarding positive integers and rational numbers when students, 6 to 9 years old in multilingual classrooms, are engaged in an algebraic learning activity proposed by the El’konin and Davydov curriculum. The main results of this study indicate that young, newly arrived students, through tool-mediated joint reflective actions as suggested in the ED curriculum, succeeded in analysing arithmetical structures of positive integers and rational numbers. When the students par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Another implementation of this model occurred in Sweden where Eriksson and Eriksson (2021) conducted a study implementing Davydov-inspired learning activities in multilingual classrooms. They found that engagement in this math curriculum led children to increased generalization and awareness of relational structures due to the way symbols arise from activity within this approach.…”
Section: Implementations Of the Elkonin-davydov Curriculummentioning
confidence: 99%
“…Another implementation of this model occurred in Sweden where Eriksson and Eriksson (2021) conducted a study implementing Davydov-inspired learning activities in multilingual classrooms. They found that engagement in this math curriculum led children to increased generalization and awareness of relational structures due to the way symbols arise from activity within this approach.…”
Section: Implementations Of the Elkonin-davydov Curriculummentioning
confidence: 99%
“…(Gattegno used the word "economical" for the advantages of his curriculum, referring to the use of children's time.) Eriksson and Eriksson (2020) conducted a study demonstrating one example of "effectiveness", which was the manner in which a Davydov-inspired learning activity led to generalisation and an appreciation of general structures, by young children in a multi-lingual context. The manner in which symbols arise from activity within Davydov's work potentially offers huge advantages in multi-lingual classrooms, and I would see this as a rich area of future research.…”
Section: Transposing a Curriculummentioning
confidence: 99%
“…Algebraic thinking is a core foundation in solving mathematical problems and is crucial in enhancing logical and analytical skills. These two aspects are closely related, as logical and analytical skills aid in detailing problem-solving steps and bridging the mathematical concepts used (Chimoni et al, 2023;Medová et al, 2020;Eriksson & Eriksson, 2021). Furthermore, algebraic thinking can stimulate the development of creative thinking by exploring mathematical concepts and encouraging open-ended questions for problem-solving (Suherman & Vidákovich, 2022;Singh & Azman, 2023).…”
Section: Introductionmentioning
confidence: 99%